ASME 2014 Small Modular Reactors Symposium 2014
DOI: 10.1115/smr2014-3392
|View full text |Cite
|
Sign up to set email alerts
|

Integration of NuScale SMR With Desalination Technologies

Abstract: Nuclear energy plants are attractive energy source for large scale water desalination since the thermal energy produced in a nuclear reactor can provide both electricity and steam to desalt water without the production of greenhouse gases. A particularly attractive option is to couple a desalination plant with the new generation of nuclear plant designs: small modular reactors (SMR). This allows regions with smaller electrical grids and limited infrastructure to add new electrical and water capacity in more ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…As shown in Figure 4, a new generation of nuclear reactors utilizes up to 1000°C, so a large amount of heat dissipation of these reactors is appropriate for different process units. The use of heat or steam from nuclear power plants in the heating of crude oil, gasoline production, or petrochemical processes is one of the examples of cogeneration systems 61 . Alonso et al's studies showed that steam from the Pebble bed modular reactor could be used for heating of crude oil with more energy efficiency 62 .…”
Section: Nuclear Cogeneration Systemsmentioning
confidence: 99%
“…As shown in Figure 4, a new generation of nuclear reactors utilizes up to 1000°C, so a large amount of heat dissipation of these reactors is appropriate for different process units. The use of heat or steam from nuclear power plants in the heating of crude oil, gasoline production, or petrochemical processes is one of the examples of cogeneration systems 61 . Alonso et al's studies showed that steam from the Pebble bed modular reactor could be used for heating of crude oil with more energy efficiency 62 .…”
Section: Nuclear Cogeneration Systemsmentioning
confidence: 99%
“…SMRs can be used for multipurpose applications and may well be safer than large-capacity reactors [5][6][7]. Some specific applications of SMRs are ship propulsion [8], small-scale power generation [9], desalinization [10], and district heating [11]. In light of climate change and the Fukushima nuclear accident, stricter regulations for fossil fuels and strengthened safety requirements for nuclear reactors have been put in place [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Another key SMR advantage to consider is the possibility to have multiples units on the same site [8,12,20]. Other factors to consider in SMR economic and financial evaluation are: suitability for cogeneration [21][22][23][24], expected higher learning rate [10,25], better adaptability to market [8], equal or higher capacity factor than current LRs [26]. Once these factors are taken into account, the capital cost is comparable between the two technologies [27].…”
Section: Introductionmentioning
confidence: 99%